Analisis Perbedaan AACR2 (Anglo-American Cataloging Rules 2nd Edition) dan RDA ((Resources Description and Access)) - Rozi, Fahrul; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
This paper was motivated by the Cataloging new guidelines RDA (Resources Description and Access) to replace AACR2 Cataloging guidelines (Anglo-American Cataloging Rules 2nd Edition) is no longer able to accommodate the development of types of library materials, so the RDA is required to accommodate the development of types of library materials. Therefore, it needs to be analyzed differences in AACR2 and RDA. Formulation of the problem is how differences AACR2 to RDA? The intention of the paper was to determine differences in AACR2 to RDA. The results of the analysis of differences in AACR2 and RDA as follows. First, the structure of AACR2 specifically describe certain library materials that have been formulated in AACR2, such as books, manuscripts, cartographic and others, while the RDA is not formulated for tetentu materials, but all the objects in the description of library materials. Second, the description of library materials based on the AACR2 identified eight areas of publication, but the RDA using flexible guidelines called core element. Third, the categories of sources or material descriptions that have been used AACR2, the GMD did not describe a clear description of the material, while RDA uses three categories in categorizing her description of the material is the media type, carrier type and content type. Fourth, the acronym has been used by such AACR2 et al., Ill., Ed., And others can not be used by the RDA. Conclusions from the analysis of AACR2 and RDA based on the results of the discussion, which AACR2 is no longer supporting the development of the literature to describe the type of information as the needs of the present. Thus, the RDA needed in the description of library materials in the present. Based on the conclusion, it can be suggested that librarians know the changes in the guidelines and implement pengatalogan in the library, so that librarians are not awkward if the guidelines are implemented. Libraries also need to prepare mengahadpi impact of such changes. Keywords: AACR2; RDA